Corps intersexes, androgynie et intermédialité dans l’œuvre des artistes Maria Klonaris et Katerina Thomadaki - Marie Vicet (Images Re-Vues)
After works focusing on self-representation and the female body, from 1982 onwards the artist duo Maria Klonaris and Katerina Thomadaki placed the figures of the hermaphrodite and the androgynous at the heart of their concerns and their plastic research. For the artists, the aim was to shift the question of the body and its representation, as well as that of the gaze, onto dissident bodies. This article examines how Klonaris and Thomadaki create new modes of appearance for the images they use in both Le Cycle des Hermaphrodites and Le Cycle de l’Ange, whether the sculpture of the Sleeping Hermaphroditus in the Louvre, the figure of Orlando or the medical photograph of an intersex person, in order to challenge gender binarity. Using the concepts of “intersexuality” and “intermedia”, which they have developed together, the artists break down both artistic categories and genders.